COVID-19 Vaccination Hesitancy among Healthcare Workers—A Review - Christopher J. Peterson; Benjamin Lee; Kenneth Nugent (Vaccines, 2022)
The COVID-19 pandemic and its associated vaccine have highlighted vaccine hesitancy among healthcare workers (HCWs). Vaccine hesitancy among this group existed prior to the pandemic and particularly centered around influenza vaccination. Being a physician, having more advanced education, and previous vaccination habits are frequently associated with vaccine acceptance. The relationship between age and caring for patients on COVID-19 vaccination is unclear, with studies providing opposing results. Reasons for hesitancy include concerns about safety and efficacy, mistrust of government and institutions, waiting for more data, and feeling that personal rights are being infringed upon. Many of these reasons reflect previous attitudes about influenza vaccination as well as political beliefs and views of personal autonomy. Finally, several interventions to encourage vaccination have been studied, including education programs and non-monetary incentives with the most effective studies using a combination of methods.